Development and Assessment of New Bioactive Glass Fiber Post. Part II: Ion’s Release - Akram M. A. Altamimi; Manhal A. Majeed (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objectives: This study was designed to develop and assess the ions release property of an innovativeexperimental bioactive fiber-reinforce composite as a new material for an intra-canal post.Study Design: An in vitro studyMaterials and Methods: Surface treated unidirectional E-glass fiber were impregnated and implanted witha triple cure, self-adhesive ACTIVA BioACTIVE resin cement to fabricate an experimental bioactive glassfiber post using hand lay-up moulding technique and polytetrafluoroethylene (PTFE) moulds, The cylindricaland rectangular form specimens were prepared, for each specimen, ensure 3min for self-cure setting, thenlight-cured for the 40s. The specimens were individually immersed in a deionized (DI) water, and sodiumchloride solution to assess the fluoride ion release, and calcium-phosphate ions release sequentially. VirginACTIVA BioACTIVE cement was used as a reference group for all investigations.Statistical analysis used: Statistical analysis was achieved by means of independent variable t-test, onewayANOVA, and Bonferroni Pairwise comparisons utilizing IBM-SPSS software.Results: Experimental material recognized a significant reduction in F-, Ca+2, and PO43- release afterreinforcement compared to virgin ACTIVA BioACTIVE.Conclusions: The ACTIVA BioACTIVE cement’s reinforcement process reduced the ion release intensityof the material but not affected the releasing pattern.